PENGARUH STRES KERJA DAN BEBAN KERJA TERHADAP PRESTASI BELAJAR MAHASISWA MANAJEMEN ANGKATAN 2016-2021 - Margareth Sylvia Sabarofek; Christine R Sawaki (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study is to find out the influence of variable work stress and workload partially and simultaneously affect the learning achievements of students management class of 2016-2021. This research is quantitative research. Samples taken in this study from a population of 75. In this study the method used in the sample technique is proportional stratified random sampling.The primary data used in the study is through filling out questionnaires and surveys directly on the research object. Secondary data in this study was obtained from books, journals and websites. The results of this study showed that variables of work stress and workload partially had a positive effect on learning achievement. As well as simultaneously variable work stress and workload have a positive effect on learning achievement. So to improve learning achievement students must have confidence and motivation that encourages to continue to strive with their ability to achieve achievements.